Symbiotic N2-Fixation Estimated by the 15N Tracer Technique and Growth of Pueraria phaseoloides (Roxb.) Benth. Inoculated with Bradyrhizobium Strain in Field Conditions - Papa Saliou Sarr; Judith Wase Okon; Didier Aime Boyogueno Begoude; Shigeru Araki; Zachée Ambang; Makoto Shibata; Shinya Funakawa (Scientifica)
This field experiment was established in Eastern Cameroon to examine the effect of selected rhizobial inoculation on N2-fixation and growth of Pueraria phaseoloides. Treatments consisted of noninoculated and Bradyrhizobium yuanmingense S3-4-inoculated Pueraria with three replications each. Ipomoea batatas as a non-N2-fixing reference was interspersed in each Pueraria plot. All the twelve plots received 2 gN/m2 of 15N ammonium sulfate 10% atom excess. At harvest, dry matter yields and the nitrogen derived from atmospheric N2-fixation (%Ndfa) of inoculated Pueraria were significantly (P<0.05) higher (81% and 10.83%, resp.) than those of noninoculated Pueraria. The inoculation enhanced nodule dry weight 2.44-fold. Consequently, the harvested N significantly (P<0.05) increased by 83% in inoculated Pueraria, resulting from the increase in N2-fixation and soil N uptake. A loss of 55 to 60% of the N fertilizer was reported, and 36 to 40% of it was immobilized in soil. Here, we demonstrated that both N2-fixing potential of P. phaseoloides and soil N uptake are improved through field inoculations using efficient bradyrhizobial species. In practice, the inoculation contributes to maximize N input in soils by the cover crop’s biomass and represent a good strategy to improve soil fertility for subsequent cultivation.